The Media Appeals Tribunal and the Protection of Information Bill as challenges to freedom of expression and good governance in South Africa - Thomas, Marie Kristie Tania (Afrika Focus, 2018)
This paper examines the Media Appeals Tribunal (MAT) and the Protection of Information Bill (PIB) as potential challenges to freedom of expression and good governance in South Africa. The modus operandi and the objectives of MAT and PIB are presented and examined to indicate whether these may act as threats to freedom of expression and good governance. This paper uses information obtained from academic articles, the South African Constitution, legislative documents, news articles as well as African and international reports. This research finds that if MAT and PIB are passed as laws without substantial amendments in favour of the genuine respect for freedom of media and press, they will potentially lead to the regression of both freedom of expression and good governance and above all, threaten democracy in South Africa. Key words: Media Appeals Tribunal, Protection of Information Bill, freedom of expression, good governance, democracy, South Africa